PENGARUH KARAKTERISTIK KEPRIBADIAN, MOTIVASI DAN KOMITMEN TERHADAP SIKAP PEGAWAI - Fajar Manganti (Jurnal Manajemen Dayasaing, 2015)
This research was conducted at the tax office in the center circle pratama Java II of theregional office of the Directorate General pajak.Judul this research is “The Influenceof Personality Characteristics,, Motivation and commitment, the attitude of Employeesin Organizational Change” The study population comprised 451 employess. Method ofsampling is purposive sampling. the samples echelon strata four of 25 respondents anda layer of non-position employees 100 respondents. “the data analysis to determine the effect of variable characteristics of personality, motivation and commitment to employee attitudes in this study were calculated using analysis Path (Path analysis).